Aircraft Maintenance Management - Role of Licence Aircraft Maintenance Engineer by Complying to Aviation Regulations to ensure a High Standard of Maintenance - Sirat, Waris; Harun, Zulkefli (2006)
Civil Aviation is a highly regulated industry. Complying to aviation regulations starts from the aircraft manufacturing process, aircraft maintenance and also the training and licensing of aircraft maintenance personal. The United Nations (UN) recognizes the International Civil Aviation Organization (ICAO) as a specialized agency for international civil aviation standards and Malaysia is one of the contracting states. Malaysia being a sovereign country has formulated its own air legislation and regulations in line with the ICAO requirements through an Act of Parliament with the introduction of The Malaysian Civil Aviation Regulations (MCAR). The MCAR through the medium of Airworthiness Notices (AN) make provision for the adoption of the code of airworthiness certification and procedural requirements published as FAR’s, JAR’s and BCAR’s as standards acceptable to DCA Malaysia. As a contracting States of ICAO, DCA Malaysia is subject to oversight (Audit) activities by ICAO to ensure compliance to ICAO Annexes, Standards, recommended practices, procedures and guidance materials. This paper will discuss the role of Licence Aircraft Maintenance Engineers (LAME) on aircraft maintenance management, the ICAO Annex 1 and DCA Malaysia Airworthiness Notices (AN) which provide information and regulation on licensing of aircraft maintenance personal including their privileges and also the establishment of UniKL MIAT to train the aircraft maintenance workforce. The stringent adherence to regulations has in fact produced a safe and airworthy aircraft for passenger comfort.